The Optimum Quantity of Money, and other Essays - Friedman, Milton (Chicago : Aldine Pub. Co., 1969)
The book professes to be about a very special problem; it is on a highly abstract and simplified level. Yet it provides a fairly comprehensive summary of the most important propositions of monetary theory
Bibliographical footnotes.
osc 25/07/2017; usc 06/09/2017
Loans
Keywords: Money supply; Monetary policy; Money